Application of strip electrode in single-gap RPC. (29th November 2021) - Li, Q.; Xie, X.; Sun, Y.; Ge, J.; Xue, Z.
Abstract: The Resistive Plate Chamber (RPC) is widely used in High Energy Physics experiments as trigger detector to take advantage of its good time resolution and high efficiency. A conventional RPC detector consists of one gas gap covered by graphite layers on both side. The working voltage is applied on these layers and the charge of avalanche dissipates through them. In this paper, a design which removes the graphite layers and uses the readout strips as the electrode is applied to simplify the structure of this detector. This design eliminates the challenge of controlling the uniformity of the graphite layer and simplifies the detector structure.